THE ANALYSIS OF DEIXIS AND IMPLICATURE IN TEACHER-STUDENT INTERACTION IN ENGLISH CLASSES - Amalia, Riska; Saili Rahmah, Leny; Satya Gumelar, Wahyu (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study examines how students and teachers communicate in English classes, with a particular emphasis on implicature and deixis usage and its impact on students' comprehension. Analyzing the effects of implicature and deixis on student interaction and comprehension is the aim of this study. Data were collected at SMKN 9 Bandung through interviews, audio recordings, and observations using a qualitative methodology. The results of the analysis demonstrated that the use of deixis including person, spatial, and temporal deixis created an interactive environment that encouraged student participation. Additionally, the teacher's use of implicature in open-ended questions prompted critical thinking and active participation from the students This study identifies the challenges students face in understanding hidden meanings and the social context that influences language use. The findings suggest that building a strong relationship between teachers and students is just as important for effective classroom communication as simply dispensing knowledge. Therefore, understanding implicature and deixis helps students become better communicators.